The single voting day: innovations of electoral legislation and legal protection of organisation of deputies elections - Shidlovsky, Andrei V.; Sukhaparau, Viktar P. (Journal of the Belarusian State University. Law, 2024)
The authors of the article analyse innovations in constitutional, electoral and information law that regulate the organisation and conduction of deputies, elections on a single voting day. The experience of deputies, elections of the House of Representatives of the National Assembly of the Republic of Belarus of the eighth convocation and deputies of local Councils of Deputies of the twenty-ninth convocation, held on 25 February 2024, is taken into account. Particular attention is paid to the principle of openness in the preparation and conduction of elections, in particular the organisation of informing voters about the progress of the election campaign, which seems topical at the present stage of digital development in the Republic of Belarus. The results of the study also reveal the conditions for ensuring public order by law enforcement legislation during the organisation and conduction of deputies, elections on a single voting day.
Keywords: single voting day; constitutional innovations; informing of voters; constituency; polling stations; election campaigning; public events; deputies elections